Analysis of Vibration Characteristics of Podded Propulsor Shafting Based on Analytical Method - Yaqi Tian; Cong Zhang; Lei Yang; Wu Ouyang; Xincong Zhou (Journal of Marine Science and Engineering, 2022)
Podded propulsors are widely used in warships and cruise ships, which have a higher requirement of vibrational and acoustic design. Therefore, studying vibration characteristics and the transmission mechanism of podded propulsor shafting is significant for reducing vibration and ensuring the safe operation of ships. This paper establishes a model of podded propulsor shafting by analytical method. The shafting is simplified to a heterogeneous variable cross-section beam, while bearings are seen as springs. The podded propulsor shafting has one radial-thrust hybrid bearing and one radial bearing. The excitations from the propeller and cabin are considered. The influences of bearing stiffness, bearing location, and excitation on vibration characteristics of shafting are analyzed. The main conclusions are as follows: Based on the analysis of the area that resonance frequency is sensitive to the change of bearing stiffness, the resonance frequencies of the shafting can be adjusted to the proper range. The large span between hybrid bearing and radial bearing leads to low stiffness of shafting and low resonances frequencies. Under radial excitations, the low vibration always occurs at the hybrid bearing, motor shafting, or propeller end of shafting. This research provides theoretical support for the design and optimization of vibration reduction of podded propulsor shafting.